(untitled) (Annals of Bangladesh Agriculture, 2022)
An experiment was conducted following randomized complete block design with three replications during boro season of 2017-2018 to estimate combining ability for 16 agronomic traits of a 5x5 half diallel populations generated by using five selected parents of rice. Analysis of variance exhibited highly significant variability among the genotypes and combining ability variances for most of the studied traits except grain length and length-breadth ratio. The results indicated that none of the parent and hybrid combination performed better as general and specific combiner for all the traits. Performances were found to vary from trait to trait among parents and hybrid combinations. Parental genotype P3 performed as the best general combiner for grain yield hill-1 (2.16**) followed by P5 (1.43**). The hybrid combination P3×P5 exhibited the best specific combiner for grain yield hill-1 (5.17**) followed by P3×P4 (5.06**). However, the GCA : SCA ratio was less than unity for panicle length, effective tillers plant-1, filled grains panicle-1, straw dry weight and grain yield hill-1 indicating the presence of non-additive gene action. The results revealed that these traits could be improved through hybridization between the parents P3 and P5. Ann. Bangladesh Agric. (2021) 25 (1) : 23-31